Arabic Language Learning Assistance Using Direct Methods at MTs Al–Barokah Jaharun B Galang - Andri Rivai; Naufal Fikri Hamdi; Rizki Hidayat; Umar Sholeh Ritonga; Rahmat Fauzi Zega; Muhammad Habib; M. Arrasyid (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
This study uses a descriptive qualitative approach with the ABCD (Asset Based Community Development) model to explore the potential problems in improving MT students' Arabic speaking skills in Jaharun B Village. Conducted on March 25-28, 2024, at MTs Al Barokah, this study involved observation, interviews, and documentation. The main focus is on the stages of learning Arabic (Maharatul Kalam) for grade 8 students with direct teaching methods (Thariqah Mubasyarah). The study results showed that this mentoring positively improved students' speaking skills in terms of fluency, pronunciation, and confidence in using Arabic. The direct method has proven effective in making learning more lively, interactive, and relevant to students' daily communication needs. Learning becomes more comprehensive and sustainable by involving community assets, such as support from parents and teachers.